Energy Efficient Photovoltaic-Electric Spring for Real and Reactive Power Control in Demand-Side Management - Kollipara, Keerthi Deepika; Vijay Kumar, J.; R, Prasanthi; Sura, Srinivasa Rao; Kumar Patnaik, M. S. Pradeep; Ravi Sankar, R. S. (Frontiers in Energy Research, 2022)
Photovoltaic-Electric Spring (PV-ES) is a promising topology to utilize widespread residential roof-top photovoltaic (PV) systems in demand-side management. In this work, extraction of maximum power from PV panel using Perturb & Observe algorithm along with boost converter are designed. This power is given as input to the DC link of Electric Spring. Extensive simulations are carried out in MATLAB/Simulink. It was confirmed that the proposed PV-ES precisely controls the active power consumption of the system and voltage regulation at PCC. Finally, the effectiveness of the proposed topology was verified for changes in PCC voltage, irradiation, and reference power.